1993
DOI: 10.1128/aem.59.10.3400-3405.1993
|View full text |Cite
|
Sign up to set email alerts
|

Influence of organic nutrients and cocultures on the competitive behavior of 1,2-dichloroethane-degrading bacteria

Abstract: The effects of organic nutrients and cocultures on substrate removal by and competitive behavior of 1,2-dichloroethane-degrading bacteria were investigated. Xanthobacter autotrophicus GJ1O needed biotin for optimal growth on 1,2-dichloroethane. In continuous culture, dilution of biotin to a concentration below 0.2 nM resulted in washout. Growth could be restored by inoculation with the 2-chloroethanol utilizer Pseudomonas sp. strain GJ1, leading to a new steady state in which about 1% of the mixed culture cons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

1994
1994
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…In addition, gas-phase enzymatic reactions held irreplaceable merits in the processing of gaseous substrates. For instance, the detection and detoxification of nerve agents, the decontamination of volatile pollutants, and the biosynthesis of ammonia from N 2 14,15 . Pioneering studies have shown that enzymes (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, gas-phase enzymatic reactions held irreplaceable merits in the processing of gaseous substrates. For instance, the detection and detoxification of nerve agents, the decontamination of volatile pollutants, and the biosynthesis of ammonia from N 2 14,15 . Pioneering studies have shown that enzymes (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…However, A. aquaticus AD25, as well as X. autotrophicus GJ10 and Pseudomonas sp. strain DE2, require vitamins for optimal growth (16,21). Therefore, we set out to isolate DCA-degrading bacteria with a high affinity for DCA but without the dependency on vitamins for optimal growth.…”
mentioning
confidence: 99%
“…strain GJi grew more stably on 1,2-dichloroethane than did strain GJ10 alone, since GJi fulfilled the requirement of strain GJ10 for biotin and GJ1 degraded the toxic compounds that accumulated from the dichloroethane-utilizing strain GJ10 under suboptimal conditions (521).…”
Section: Application Of Microbial Systems In Environmental Protectionmentioning
confidence: 98%